Non‐contact low‐frequency ultrasound therapy compared with UK standard of care for venous leg ulcers: a single‐centre, assessor‐blinded, randomised controlled trial. Issue 5 (25th January 2015) - White, Judith; Ivins, Nicola; Wilkes, Antony; Carolan‐Rees, Grace; Harding, Keith G
Abstract: 'Hard‐to‐heal' wounds are those which fail to heal with standard therapy in an orderly and timely manner and may warrant the use of advanced treatments such as non‐contact low‐frequency ultrasound (NLFU) therapy. This evaluator‐blinded, single‐site, randomised controlled trial, compared NLFU in addition to UK standard of care [SOC: (NLFU + SOC)] three times a week, with SOC alone at least once a week. Patients with chronic venous leg ulcers were eligible to participate. All 36 randomised patients completed treatment (17 NLFU + SOC, 19 SOC), and baseline demographics were comparable between groups. NLFU + SOC patients showed a −47% (SD: 38%) change in wound area; SOC, −39% (38%) change; and difference, −7·4% [95% confidence intervals (CIs) −33·4–18·6; P = 0·565]. The median number of infections per patient was two in both arms of the study and change in quality of life (QoL) scores was not significant ( P = 0·490). NLFU + SOC patients reported a substantial mean (SD) reduction in pain score of −14·4 (14·9) points, SOC patients' pain scores reduced by −5·3 (14·8); the difference was −9·1 ( P = 0·078). Results demonstrated the importance of high‐quality wound care. Outcome measures favoured NLFU + SOC over SOC, but the differences were not statistically significant. A larger sample size and longer follow‐up may reveal NLFU‐related improvements not identified in this study.